Big Data: How Public Response to Islamic Economy in Indonesia during Pandemic? - Dian Rizqi Khusnul Khotimah (Department of Islamic Economics, IPB University, 2022)
The social and economic impacts caused by the COVID-19 pandemic greatly affect the level of community welfare. The government has designed and implemented various programs in the context of poverty eradication during the pandemic, including increase the role of sharia or Islamic economics. Contribution of Islamic economy can strategically beneficial for Indonesia’s current and future economy. The benefits obtained by target community need to be measured as a reflection of the success of Islamic economy program and for government evaluation. Big data through social media analysis can be empowered to gain public perceptions of Islamic economy. Therefore, in this study the Twitter social media analysis approach will be used to obtain public responses regarding Islamic economy. The tweet data was collected from January 1, 2020 to June 30, 2021. The processed data is sourced from all Twitter users with tweets related to the keywords ‘ekonomi syariah' or sharia economy, 'ekonomi digital’ or digital economy, ‘keuangan syariah’ or sharia finance, and ‘industri halal’ or halal industry. Those data were analyzed using text mining method. The results of this study indicate that in general the public response accepts and supports Islamic economy in Indonesia. Those analysis result can be used as evaluation material and input for the government in making the next policy for accelerate economy recovery in pandemic era.